Intra-individual floral variation improves male fitness in a hummingbird-pollinated species - Paglia, Isis; Pinto, Alessandra Ribeiro; Amorim, Felipe W. [UNESP]; Arceo-Gómez, Gerardo; Freitas, Leandro (Elsevier, 2023)
Intra-individual variation in floral traits is widespread but yet poorly understood. Variations in flower size within individuals can have implications for plant reproductive success, hence may be under pollinator-mediated phenotypic selection. Most studies on pollinator-mediated selection only evaluate female reproductive success, although floral traits can be under stronger or opposing selection via male fitness. Here we evaluated selection on intra-individual variation and integration of floral traits via its effects on male reproductive success (pollen removal) on a hummingbird-pollinated species. We sampled flowers of Justicia sebastianopolitanae that were exposed to pollinators for 24 h and counted the number of pollen grains that remained in the anthers. We measured corolla length, corolla tube length, anther, and stigma height, as well as herkogamy, display size, and estimated the coefficient of variation (CV) of traits for each individual. We found that the greatest variation in floral traits occurs within individuals. Although intra-individual variation in anther height positively affected pollen removal, we did not detect significant selection, implying that intra-individual variation is not a target for pollinator-mediated selection through male fitness in this plant population. We also found selection on the mean of anther height, indicating the importance of the spatial separation between male and female structures. The variation in anther height may increase the area of pollen deposition on the pollinator's body. Therefore, intra-individual variation could increase the chance of an individual's pollen reaching more stigmas with different heights. We highlight that intra-individual variation should be more widely studied in the context of pollinator-mediated selection and its importance for the reproductive success of individuals in a population.
Keywords: Floral traits; Male success; Phenotypic integration; Pollination; Pollinator-mediated selection; Within-individual variation